Field studies on the Development and impact of drug resistant animal trypanosomes in market oriented production systems in the Southern Guinean zone of West Africa - McDermott, John J.; Sidibe, I.; Bauer, B.; Diarra, B.; Clausen, Peter-Henning; Woitay, T.; Ouédraogo, T.; Kamuanga, M.; Peregrine, A.S.; Eisler, M.C.; Mehlitz, D. (European Union, 2000)
To investigate the importance of trypanosomosis, resistance to trypanocidal drugs and the potential impact of integrated control measures on these factors, a 3-phase study was initiated. The first phase was a cross-sectional study in which tsetse apparent density, cattle trypanosome prevalence, trypanocidal drug use and livestock husbandry data were collected from 45 (of 166) randomly-sampled villages in all 4 livestock production systems in Kenedougou province. This study was conducted from mid-June to mid-August 1998. The second phase studied the occurrence of trypanocidal drug resistance in villages with high trypanosomosis risk (10 percent trypanosome prevalence). In 10 such villages, cattle were block treated with isometamidium at 1 mg/kg body-weight (bw) and followed at 2-weekly intervals for trypanosome infections by the buffy-coat phase-contrast technique. Trypanosomes isolated from cattle both before and after the block treatment were assessed for resistance to isometamidium and diminazene in mice. This study was conducted from mid-November 1998 to mid-February 1999. A third phase will investigate variations in livestock production parameters associated with different drug-resistance levels. This paper Reports on the results from the first two phases.